Forest spill over effects of butterfly community into different agriculture landscapes - Satimurty, Sathiyarubini (2019)
Forest conversion into agricultural land has become a major concern in South East Asia due to its negative impact on overall biodiversity specifically insects. Insects may adapt and survive under human dominated landscapes as seen in some species of butterflies (Insecta:Lepidoptera). However, most butterfly species experience population decline as a result of land use changes. The present study was conducted to investigate forest spillover effect of butterfly community into different agricultural landscapes namely rubber plantation, oil palm plantation and fruit orchard. The study was conducted at Kampung Ulu Sepri, Kampung Empangan Batu and Kampung Batang Sepri located in Pedas, Negeri Sembilan. Butterfly sampling was conducted using active and passive sampling. in all study sites (a total of 90 sampling points). For active sampling, butterflies were observed based on point count method using binocular and camera for 10 minutes at each point. Meanwhile, for passive sampling, butterfly trap with fruit bait were placed at two meter above ground for all sampling points. Habitat quality characteristics between agricultural landscape were also assessed by measuring canopy openness and closure, vegetative structure, air temperature, relative humidity and proximity to forest between different agricultural landscape. In overall, a total of 1608 Lepidoptera individual belonging to 61 species and 5 families were recorded. The results recorded the highest butterfly abundance in oil palm with 600 individuals followed by rubber plantations and fruit orchard with 585 and 423 individuals, respectively. For butterfly species richness, rubber plantation represent the highest species recorded with 24 species followed by orchard and oil palm with 22 and 15 butterfly species, respectively. Greater butterfly abundance and species richness in monoculture plantations compared to polyculture landscapes indicates spillover of butterfly community into adjacent agricultural landscapes. This study provide evidence of butterfly spill over from forest into agricultural lands. Therefore, agricultural management in monoculture plantations should emphasize on biodiversity friendly management systems by reducing agrochemical applications to help maintain butterfly resilience in human dominated landscape.